Antioxidant-mediated neuro-protective and GABAergic calming effect of Stephania japonica - Islam, Muhammad; Khatun, Mst. Julia (International Journal of Medicine, 2017)
Stephania japonica, a tropically-habituated plant is widely distributed in Bangladesh. Traditionally, it has been used in the treatment of inflammation, asthma, fever, sleep disturbance, painful conditions, and rheumatism. However, scientific evidence of its biological activities are very limited. This study evaluated neuroprotctivity along with a possible anxiolytic-like effect of the methanol leaf extract of S. japonica (MSJ). The antioxidant test was performed by using the scavenging capacity of hydroxyl (â—OH) and nitric oxide (â—OH) radicals; and an inhibition of lipid peroxidation assay. In vitro, egg albumin denaturation (IELD) and anti-acetylcholinesterase (anti-AChE) tests were performed to evaluate the anti-inflammatory and anti-cholinesterase activity, respectively. Additionally, a possible anxiolytic action of the MSJ was investigated in Swiss mice by taking diazepam (DZP) and flumazenil (FLU) as gamma amino butyric acid (GABA) receptor agonist and antagonist, respectively. The MSJ concentration (50-200 Âµg/mL)/dose (50-200 mg/kg, oral)-dependently exhibited antioxidant, anti-inflammatory, anti-AChE and anxiolytic-like effects. The MSJ also increased the activities of the standards used in antioxidant and anti-AChE (trolox), anti-inflammatory (acetyl salicylic acid), and anxiolytic (DZP: agonist) test. The MSJ exhibited antioxidant and anti-inflammatory activities. It also potentiated the action of DZP, while antagonizing the effect of the FLU, suggesting a possible GABAergic, DZP-agonistic anxiolytic-like action in experimental animals. S. japonica may be one of the good sources of neuroprotective phytochemicals.